Early Experience of Percutanious Coronary Intervention in The Cardiology Department of Chittagong Medical College Hospital, Chattogram - Awal, Anisul; Al Mamun, Kazi Shamim; Dey, Asish; Chowdhury, Ibrahim; Das, Prabir Kumar; Tareq, Nuruddin; Shaheen, Abul Hossen; Das, Sandipon (Journal of Chittagong Medical College Teachers' Association, 2020)
Background : Percutanious Coronary Intervention (PCI) is one of the popular methods of revascularization for coronary artery disease. Worldwide PCI cases increasing day by day & which reduce the need for Coronary Artery Bypass Grafting (CABG) of many patients. Aim of the study is to see the early success of Percutanious Transluminal Coronary Angioplasty (PTCA) cases performed in CMCH with their inhospital and short term outcome. Materials and methods : It is prospective observational study and an early report of ongoing study. We tested 150 patients from July’14 to May’17 in cardiology ward of CMCH. Acute Coronary Syndrome (ACS) patients are diagnosed in hospital. After initial stabilization of ACS patients, Coronary Angiogram (CAG) was done within 2-6 weeks after discharge. Significant symptomatic lesions treated by Percutanious Transluminal Coronary Angioplasty (PTCA). Assess the patient during procedure and subsequent inhospital stay and follow up at 1, 3 month after discharge. Results : The study population consisted of 150 patients (116 men and 34 women) with a mean ± SD age of 51.79 ± 8.6 years. ACS patients diagnosed as Myocardial infarction (35), NSTEMI (11) & UA (29). CAG shown 107 patients single, 30 double lesion & 13 total occlusions. PTCA were done through femoral (98 patients) and Radial (52) approach. Most of the patients need predilatation (134) before stent implantation. DES (Drug Eluting Stent) for 70.4% were deployed in most of the patients, Bere Metal Stents (BMS) deployed rest of the patient (30.6%) and Double stents needed 28 patients with mean diameters (mm) 2.89+02 and mean leangth of 14.68 mm+2. TIMI Grade 03 flow was in 104 patients (69.3%). All the stent implantation procedures were successful except one. 148 patients cured & discharge successfully. 2 patients died (1.3%) due to acute stent thrombosis and coronary artery perforation. One case (0.6%) of coronary artery dissection was managed conservatively by Eptifibatide (Intregrelin). Other complications like- Cardiogenic shock (6), hypotension (10) arrhythmia (2 cases VT) and cardiac arrest (1) managed successfully. Minimum local complication at vascular access site (Bleeding, Hematoma, etc.) was 2.6%. Subsequent follow up (1, 3 months) shows significant improvement of quality of life and no mortality. In contrary, Jeroudi et al demonstrated PTCA angiographic and clinical success in 50 and 49 patients, respectively out of 54 octo- genarian patients (93% and 91%, respectively). In our study angiographic and clinical success rate 92%, 94.6% respectively out of 150 patients. Conclusion : This is relatively new centre with limited resource & facility. Early result is encouraging. PCI is the choice of revascularization of modern cardiac era. JCMCTA 2020 ; 31 (2) : 31-36